Evidence for phonological constraints on nuclear accent placement - German, James (2014)
In lieu of an abstract, here is a brief excerpt of the content: Evidence for phonological constraints on nuclear accent placement* JAMES GERMAN JANET PIERREHUMBERT STEFAN KAUFMANN Northwestern University Northwestern University Northwestern University 1.